2022
DOI: 10.1186/s12885-022-10377-x
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram for prediction of prolonged postoperative ileus after colorectal resection

Abstract: Background Prolonged postoperative ileus (PPOI) is a major complication in patients undergoing colorectal resection. The aim of this study was to analyze the risk factors contributing to PPOI, and to develop an effective nomogram to determine the risks of this population. Methods A total of 1,254 patients with colorectal cancer who underwent radical colorectal resection at Fujian Cancer Hospital from March 2016 to August 2021 were enrolled as a tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…reported an incidence of PPOI of 19.75% in gastrectomy for gastric cancer [5], while Lind et al showed an incidence of 10.2% by analyzing 1254 patients with colorectal cancer [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reported an incidence of PPOI of 19.75% in gastrectomy for gastric cancer [5], while Lind et al showed an incidence of 10.2% by analyzing 1254 patients with colorectal cancer [10].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, these models make a signi cant contribution to the development of strategies to reduce or prevent the occurrence of PPOI. However, to our knowledge, few studies have used nomogram prediction models to assess the risk of PPOI after colorectal surgery, especially in patients undergoing rectal surgery [5,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Various risk factors for development of POI have been identi ed including increasing age, hypokalaemia, hypo-proteinemia, renal failure, peritoneal sepsis, American Society of Anesthesiologists scores 3 to 4, open approach, operative di culty, longer operative duration, bowel handling, drop in hematocrit or need for a transfusion, increasing crystalloid administration, intraoperative uid overload and delayed mobilization. [9,11] In its pathological form it can potentially result in increased nausea and vomiting, increased postoperative pain, pulmonary complications, poor wound healing, delayed oral intake, delay in postoperative mobilization, increased length of hospital stays (LOHS), increased resource use and healthcare costs. [9,10,12,13] Hence, it merits attention of researchers.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, Gleason sum and HALP were found to be particular risk factors for progression-free survival in metastatic PCa patients who underwent cytoreductive radical prostatectomy by Guo et al 27 The nomogram has been used extensively by oncologists to produce prognostic information for specific patients owing to its intuitive design and statistical probability. 28,29 With the aid of multivariate Cox regression analysis, an unique nomogram was created in this work by combining the severe LUTS, HALP score, and Gleason sum. The combined nomogram worked well as an all-encompassing scoring system for predicting the progression of CRPC, the calibration curve and C-index (0.794, 95% CI: 0.759-0.829 and 0.816, 95% CI: 0.757-0.875 for the training and validation cohorts, respectively) provided support for this prediction.…”
Section: Discussionmentioning
confidence: 99%